File Now, Pay Later. - Gunderman, R.D.
This paper discusses provisional patent application. The Provisional Application for Patent was introduced a dozen years ago to make initial patent protection more affordable to small businesses. It gets you to "patent pending" status faster and cheaper than a standard, or "utility" patent application. It also gives a whole extra year of patent-pending status without sacrificing a single day of the life of any patent that may issue from it. The dangers of filing a provisional patent application are also discussed
Keywords: US Patent and Trademark Office; USPTO; Initial patent protection; Patent-pending status; Provisional patent application